PENGARUH PENAMBAHAN INOKULUM Saccharomyces cerevisiae DAN LAMA FERMENTASI TERHADAP KARAKTERISTIK CUKA FERMENTASI DARI CAIRAN PULPA HASIL SAMPING FERMENTASI BIJI KAKAO (Theobrama cacao L.) - Mahasari Putri, Anak Agung Sagung Inten; Putra, G.P. Ganda; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 3 (2016): September)
This aims to this study was to (1) determine the effect of addition inoculum  Saccharomyces cerevisiae  and fermentation period on the characteristics of vinegar fermentation  from liquid waste of cacao beans fermentation, and (2) to determine the accurate of  addition innoculum  Saccharomyces cerevisiae  and fermentation period which one produces the best characteristic fermentation  from liquid waste of cacao beans fermentation. The experiments was designed by a Split Plot design with the addition of inoculum  Saccharomyces cerevisiae  (S) into the main plot consisting of 3 plots 10%, 15%, and 20% (v/v). Fermentation period (H) is a subplots consisting of 6 levels were 0, 5, 10, 15, 20, 25 days. The fermentation period was affected significantly (P <0,01) on levels of acetic acid, total acid, alcohol content, total sugar and total dissolved solids from a liquid pulp vinegar fermentation  from liquid waste of cacao beans fermentation, while the addition of inoculum  Saccharomyces cerevisiae and interaction did not affect (P> 0,05). The best characteristics of fermentation vinegar was found on the addition of an inoculum of 10% and fermentation period for 25 days  with the, acetic acid content, total of acid, alcohol content, total sugar and total of soluble solid were  2,86 (% v/v), 1,16 meq NaOH / g, 0,00%, 1,29%, dan 6,02 o Brix, respectively. Keyword : vinegar fermentation, cacao, watery sweating, fermentation period, additional of inoculum.
Keywords: 108,